TYPES AND FEATURES OF INTELLIGENCE TESTS - Narkulov , Xusan Ismoilovich (Educational Research in Universal Sciences, 2024)
According to scientific psychological sources, intelligence is derived from the Latin word, which usually means more intelligent understanding, understanding, understanding. It seems to us that intelligence consists in the structure of a complex of a person’s to some extent solid, stable mental abilities. As you know, the diagnostic significance of any psychological test depends on its satisfaction of several general requirements, including standardization, reliability, validity.